Behavioural response of crossbred (Landrace × Desi) pigs under different floor space allowances - KASWAN, SANDEEP; PATEL, B H M; MONDAL, S K; KUMAR, SANJAY (The Indian Journal of Animal Sciences, 2018)
Present investigation was carried out to study the behaviour of pigs at 33 and 50% reduced floor space allowances in relation to Indian standards (IS: 3916-1966) for housing of pigs. Crossbred (Landrace × Desi) barrows (36) were reared with 3 different floor space allowances (n = 4 (group size) × 3 (replications) = 12 each) i.e. group TIS (control) had floor space allowance as per Indian standards, while T2/3 and T1/2 treatment groups had 33 and 50% reduced floor space allocation per pig. Accordingly, during weaner (6–14 weeks), grower (15–22 weeks) and finisher (23–28 weeks) stages, 3 different floor spaces were provided. During each growth stage (weaner/grower/ finisher), activities of each unit (consisting of 4 animals) were recorded thrice in sessions of 2 consecutive hours (an hour before (preprandial) and after (prandial and postprandial) offering of second meal in afternoon). Total time spent in agonistic activities did not differ among the groups. However, parallel pressing agonistic activity was more in T1/2 group during grower and finisher stages at prandial and postprandial time while in TIS group during weaner stage at preprandial time. Time spent resting was higher in TIS group at prandial and postprandial time during weaner stage while it was higher in T2/3 group during grower stage. Exploratory activities and social interactions were maximum in T2/3 group during weaner and finisher stages and differed significantly from T1/2 group. From behavioural response, it can be concluded that suitable floor space allowance should lie in between 33 to 50% reduction in relation to IS specifications.